2012
DOI: 10.1103/physrevb.86.161303
|View full text |Cite
|
Sign up to set email alerts
|

Hole spin mode locking and coherent dynamics in a largely inhomogeneous ensemble ofp-doped InAs quantum dots

Abstract: In this study, we evidence hole spin mode locking in a largely inhomogeneous p-doped InAs quantum dot (QD) ensemble, g h x /g h x ≈ 34%, which allows us to reveal a long spin coherence time of T h 2 ≈ 0.8 μs. In addition, with a two-pump experiment, we demonstrate, in a low magnetic range 60-120 mT, the possibility to synchronize and tune a single subset of QDs through the distribution. Experiments are supported by an analysis within the density matrix approach.The resident spin of a carrier confined in a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…j values obtained in n-doped 12,14 or p-doped QDs. 15 At B ¼ 0 T, at very small concentration, and because of the localization of the donor-bound electron spins, their dephasing time is likely to be determined by hyperfine interaction. 16,17 The studied A 0 X shows a binding energy of % 12 meV.…”
Section: Resultsmentioning
confidence: 99%
“…j values obtained in n-doped 12,14 or p-doped QDs. 15 At B ¼ 0 T, at very small concentration, and because of the localization of the donor-bound electron spins, their dephasing time is likely to be determined by hyperfine interaction. 16,17 The studied A 0 X shows a binding energy of % 12 meV.…”
Section: Resultsmentioning
confidence: 99%
“…For the holes, the hyperfine interaction was found to be about an order of magnitude weaker, as evidenced also from the relative strength of the corresponding signals at negative delays. Therefore, longer coherence times were expected for the hole spins, which could not be confirmed .…”
Section: Measurement Of Spin Coherent Signalmentioning
confidence: 92%
“…2 that the phase φ is not constant, as would be expected from the simplified picture, but changes from zero in the high field limit to φ = π/2 when the magnetic field intensity B approaches zero, which is precisely when the fast dephasing approximation fails. Notice also that recently it was demonstrated that the hole spin coherence lifetime is typically 800 ns [14], which exceeds by three orders of magnitude the characteristic trion recombination time of τ , which is in the nanosecond range [12]. Therefore, an accurate description of the phase of the long-term magnetization oscillation requires modeling the precession of both electrons and holes, which can be obtained by resolving the time-dependent Schrödinger equation.…”
mentioning
confidence: 98%